Internal or External Financing: New Evidence on Investor Reaction in Indonesian Manufacturing Firms - Rifki Fikasari; Yustrida Bernawati (Journal of Accounting and Investment, 2021)
Research aims: This study aims to examine investor reaction to financing sources due to its pecking order theory hierarchy.Design/Methodology/Approach: This research used a purposive sampling method of manufacturing listed firms on the Indonesia Stock Exchange, which were tested utilizing Ordinary Least Square and SPSS software.Research findings: The results showed that the investor reacted negatively to internal financing measured by the firm's retained earnings. Conversely, this research found that investors reacted positively to external financing in measurement, leverage, and equity issuance. Furthermore, the results revealed that leverage had a more positive reaction than equity issuance.Theoretical contribution/Originality: This research contributes to the pecking order theory literature to test how investor reacts to which source of financing is chosen due to its hierarchy. There is evidence that Indonesian manufacturing firms had inadequate internal financing, which made investors react negatively, and investors tended to choose leverage over equity as external financing.Practitioner/Policy implication: Our study contributes to the firm's management to carefully choose financing sources to fulfill the investor interest. This research also suggests that the firm produces more profit to provide adequate internal source financing as the research results showed that investors preferred internal than external financing. Furthermore, when there is inadequate internal financing, the firm's management should use leverage over equity.Research limitation/Implication: First, our study employed total liability rather than debt to leverage measurement. Second, our study only provided evidence of negative reactions to show that the firm failed to provide adequate internal financing sources rather than examined the level of adequate internal financing sources.